THEORY AND PRACTICE OF BIM TECHNOLOGY IN PROJECT OF PREFABRICATED BUILDING - A SYSTEMATIC REVIEW - Jia, Kun; Syamsunur, Deprizon; binti Surol , Saliha; Wahyuni, Putu Ika; Nelfia, Lisa Oksri; Bt Md Noh, Nur Ilya Farhana; Lin Ng, Jing; Ardana, Putu Doddy Heka (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2024)
Prefabricated buildings represent a novel approach to construction, characterized by standardized designs, factory-based processing, and assembly-line operations. Over the recent years, the continuous advancement and maturation of BIM (Building Information Modeling) technology have fostered advantageous conditions for the enhancement and transformation of the construction sector. Prefabricated buildings integrate a variety of digital technologies to break down barriers in various links of the traditional construction industry. This approach effectively fosters information sharing and resource substitution across different stages and among various stakeholders in construction, thereby preventing issues such as inadequate information communication that often arise during the building process. This review elucidates the prevalent employment of BIM technology in PB (prefabricated buildings) through a systematic literature review and content analysis. A three-stage systematic literature review approach was adopted to identify and review 81 relevant articles, culminating in a summary outlining the contribution, development trends, and restriction of BIM technology in PB. The review also emphasises the potential of BIM technology, but the need for effective integration of the technology to improve future prefabrication practices